Need help on solving three system of equations using substitution? -x-y-z=-9 -5x+5y+6z=8 3x+3z=5 I really need help...

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Need help on solving three system of equations using substitution? -x-y-z=-9 -5x+5y+6z=8 3x+3z=5 I really need help...

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

This is confusing....
Somebody please help me...
x-y-z=-9 z = -9 -x + y Using this: 3x+3z=5 3x + 3(-9 -x +y) = 5 3x -27 -3x +3y = 5 3y - 27 = 5 3y = 32 y = 32/3 x - 32/3 - (-9 - x + 32/3) = -9 x - 32/3 + 9 + x - 32/3 = -9 2x - 12.3 = -9 2x = 3.3 x = 1 2/3 z = -9 - 1 2/3 + 32/3 z = 0 1 2/3 - 32/3 - 0 = -9

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Thanks for helping
R u sure these how you do them
Best Response 0 x-y-z=-9 z = -9 -x + y Using this: 3x+3z=5 3x + 3(-9 -x +y) = 5 3x -27 -3x +3y = 5 3y - 27 = 5 3y = 32 y = 32/3 x - 32/3 - (-9 - x + 32/3) = -9 x - 32/3 + 9 + x - 32/3 = -9 2x - 12.3 = -9 2x = 3.3 x = 1 2/3 z = -9 - 1 2/3 + 32/3 z = 0 1 2/3 - 32/3 - 0 = -9
Thanks
welcome
That was quick
yep
Can you add her people as friends
here
who you talking about
Oh nothing..never mind
oh ok
How did you get 12.3

Not the answer you are looking for?

Search for more explanations.

Ask your own question